The Relationship between HbA1c, GDP and Disease Duration on the Occurrence of Diabetic Neuropathy at Ibnu Sina Hospital - Jannah, Miftahul; Hidayati, Prema Hapsari; Mulyadi, Farah Ekawati; Kartika, Irna Diyana; Irmayanti, Irmayanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Diabetes Mellitus (DM) affects over 693 million adults globally by 2045, with complications like neuropathy underscoring the need for effective monitoring. This observational case-control study at Ibnu Sina Hospital, Makassar, explores the relationship between HbA1c levels, fasting blood sugar (GDP), disease duration, and diabetic neuropathy. Analyzing 77 medical records, the study found that most participants were aged 56-65 years, predominantly male, with high rates of uncontrolled HbA1c (80.5%) and GDP (67.5%). Diabetic neuropathy prevalence was 61.0%. Statistical analysis revealed significant correlations between neuropathy and HbA1c levels (p=0.000), GDP (p=0.002), and disease duration (p=0.041). These findings highlight the impact of glycemic control and disease duration on neuropathy in DM patients.